Self-Nanoemulsifying System Loaded with Sildenafil Citrate and Incorporated within Oral Lyophilized Flash Tablets: Preparation, Optimization, and In Vivo Evaluation - Khaled M. Hosny; Nabil A. Alhakamy; Maeen A. Almodhwahi; Mallesh Kurakula; Alshaimaa M. Almehmady; Samar S. Elgebaly (MDPI AG, 2020)
Sildenafil citrate is a drug used throughout the world primarily to treat erectile dysfunction. Several problems with the commercially available product decrease its efficacy, such as limited solubility, delayed onset of action, and low bioavailability with a large variability in the absorption profile. This study aimed to develop an optimized self-nanoemulsifying lyophilized tablet for the drug to conquer the foresaid problems. Sildenafil solubility in various surfactants, oils, and cosurfactants was attempted. An optimized formulation of a loaded self-nanoemulsion with a small droplet size was developed by applying a special cubic model of the mixture design. Sixteen formulations were prepared and characterized for droplet size. On the basis of solubility studies, a clove oil/oleic acid mixture, polysorbate 20 (Tween 20), and propylene glycol were selected as the proposed oil, surfactant, and cosurfactant, respectively. On the basis of desirability, an optimized sildenafil citrate-loaded self-nanoemulsifying delivery system containing 10% of the oil mixture, 60% of the surfactant, and 30% of the cosurfactant had a droplet size of 65 nm. Subsequently, the tablet form was fabricated with optimum ratios of 0.4% fumed silica, 0.1% hydroxypropyl methylcellulose, and 0.4% sodium starch glycolate. This formula showed satisfactory results in both disintegration and dissolution studies. In vivo pharmacokinetic studies indicated a higher bioavailability (1.44 times) and rapid absorption profile for the study's tablets compared with commercially available tablets. In conclusion, highly bioavailable oral lyophilized flash tablets of sildenafil were successfully prepared. They will be a good alternative to the conventional solid-dosage form.